Cutting‐Edge Nanomaterials for Advanced Multimodal Bioimaging Applications. Issue 1 (18th December 2017) - Tsang, Ming‐Kiu; Wong, Yuen‐Ting; Hao, Jianhua
Abstract: The desire for high sensitivity, resolution, low toxicity, and fast clearance contrast agents has driven the research for new nanomaterial systems. The drawbacks of traditional molecular probes limit their bioimaging ability, hence the exploration of emerging nanomaterials for multimodal bioimaging continues with rational designs. The key for realizing effective multimodal bioimaging is harnessing the physical and chemical properties of the nanomaterials. Although some nanomaterials possess multimodality intrinsically, those imaging modes may not be sufficient to meet the increasing demands of various applications. Therefore, the fabrication of novel composite structures by integrating various nanomaterials or molecules may overcome the challenging issues in multimodal bioimaging. An overview and considerations for multimodal bioimaging and the requirements regarding the nanomaterials are presented. The recently emerged nanomaterials and their composite structures for multimodal bioimaging are highlighted, including the recently emerging 2D materials. The traditional nanomaterials also show breakthroughs in terms of novel structures and morphologies, which would affect the contrast ability, entrance, and clearance from the in vivo models. Finally, some suggestions for toxicity studies of nanomaterials and new strategies are presented for realizing the advance of multimodal bioimaging. Abstract : The interest in visualizing biological structures is driving the search for cutting‐edge nanomaterials. An ideal nanoprobe should possess high sensitivity, high resolution, low toxicity, and fast clearance. The emerging and recent nanomaterials for multimodal bioimaging are highlighted. Moreover, the suggestions for toxicity studies and future development are presented for realizing the advance of multimodal bioimaging.